New issues in International crisis management/ edited by Gilbert R. Winham - Wihham, Gilbert R. (ed.) (London, 1988)
A comprehensive overview of the state of crisis management in interna tional affairs, this book focuses primarily on the US-USSR relationship. For most of the postwar period, the U.S. superiority in nuclear weapons shaped the political structure within which interna onal crises occurred. This edge began to deteriorate by the late 1970s, leading to a new and potentially more dangerous structure within which the superpower rivalry is now conducted. Arguing that the shifting nuclear balance has created a new dimension for crisis management, the contributors analyze such issues as the informal norms of diplomatic behavior that have evolved during the extended superpower rivalry, the tendency of both superpowers to engage in activities that progressively reduce crisis stability, and various concrete measures such as risk reduction centers that might enhance the current system for crisis management. The book also includes case studies of crisis management among non-superpowers. Taken together, these papers address the important question of how human control can be maximized in situations of international crisis.